Is the «Ministry of Happiness» the First and only Task of Good Government towards Strengthening the Rule of Law in Public Administration? - M. V. Anisiforova (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
Problems, including chronic administrative ones, in the public administration system are being studied by many management experts. Some, if not all, of these problems are linked to the lack of a common conceptual framework for their resolution, as well as a lack of unified approaches agreed upon with civil society regarding the areas (or, if you will, the breakthrough areas) where the state should focus its primary efforts and resources within public administration. The increasing frequency of appeals to the idea of creating a «ministry of happiness» worldwide, and in the Russian Federation in particular, has prompted reﬂection on this topic and an attempt to assess the viability and feasibility of implementing such a proposal.